Analisis Potensi Bahaya dan Penilaian Risiko Keselamatan dan Kesehatan Kerja (K3) Menggunakan Metode Hazard Identification, Risk Assessment, and Risk Control (HIRARC) dan Job Safety Analysis (JSA) di Konveksi Gunung Puntang - Reza Abdul Rohman; Bambang Handoko (Indo Publishing, 2026)
The garment industry is one of the manufacturing sectors with various occupational hazards, including mechanical, ergonomic, physical, chemical, and fire hazards, which may increase the risk of workplace accidents if not managed effectively. Therefore, a systematic approach is required to identify hazards, assess risks, and determine appropriate control measures. This article aims to review the implementation of the Hazard Identification, Risk Assessment and Risk Control (HIRARC) and Job Safety Analysis (JSA) methods to improve occupational safety and health in the garment industry. This study employed a literature review method by analyzing scientific articles, books, standards, and regulations related to the implementation of HIRARC and JSA in the manufacturing sector. The findings indicate that the HIRARC method effectively identifies workplace hazards, evaluates risk levels based on likelihood and severity, and determines control priorities according to the hierarchy of risk control. Meanwhile, the JSA method provides a more detailed analysis of each work activity, enabling more specific identification of potential hazards. The integration of HIRARC and JSA is considered effective in supporting occupational safety and health management systems by minimizing workplace accident risks, improving worker safety, and enhancing productivity in the garment industry..